The Effect of Work-Life Balance on Higher Education Employee Performance: Moderation of Organizational Support and Job Satisfaction Level - April Gunawan Malau (Yayasan Keluarga Guru Mandiri, 2023)
This study examines the effect of work-life balance on employee performance in higher education institutions, especially maritime education and training institutions in Jakarta. In addition, organizational support and job satisfaction were chosen to moderate the WLB relationship and the employee's performance. Using data from 197 respondents in fiveinstitutions, this study processed the data using principal component factor analysis (PCFA) and ordinary least squares (OLS) regression. The test results show that two of the three research hypotheses are accepted. First, WLB is empirically proven to have a positive effect on employee performance. Second, job satisfaction strengthens the positive relationship between WLB and employee performance. Third, organizational support is not proven to moderate the WLB relationship and employee performance. The findings in this study indicate that WLB enables employees to carry out personal and work obligations effectively and efficiently. Employees who can do that will be able to fulfill their commitment to providing the best for the organization where they work. However, in practice, organizations are sometimes unable to understand the complexities of each employee's personal life, so the support provided is not following the needs of employees. Finally, despite all the limitations, this research has academic and practical implications because research attempting to moderate WLB on employee performance is still rare. The practical implication is that higher education leaders must understand the needs of employees so that they can balance their personal and work lives.